Effect of a home medication review program on medication adherence, HbA1c, fasting blood sugar, blood pressure, and lipid profiles in patients with type 2 diabetes mellitus: a randomized controlled trial. - Alias, Nor Elina; Zin, Che Suraya; Ball, Patrick (2014)
Poor medication adherence diminishes the health benefits of pharmacotherapies. Patients with Type 2 Diabetes Mellitus (T2DM) require treatment with multiple medications, placing them at increased risk for nonadherence. This study aimed to investigate the efficacy of a home medication review program conducted by a pharmacist to improve medication adherence and its associated effects on HbA1c, fasting blood sugar (FBS), blood pressure (BP), and lipid profiles.